Citizen's advocacy guide a guide to the 11th Philippine Congress. (Center for Legislative Development, 1999)
Aimed at providing information to assist civil society organizations in understanding the structure and powers of the congress, the guide contains information on the congress' key players, legislative processes and how advocates can influence the legislation, different ways to access information about the congress, initial assessment of the 11th congress- its capacity and potentials. The guide also serves as a handy reference on "who's who" in the 11th congress by providing a profile on each member of the congress, including a survey of their relatives in politics and economic interests. It also provides an overview of the agenda and organization and procedure in Congress.